1999
DOI: 10.1177/03635465990270040301
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging, Antiinflammatory Drugs, and Ultrasound on the In Vitro Response of Tendon Tissue

Abstract: We investigated the effects of aging and various treatments on rat patellar tendon using an in vitro model. In the first part of the study, the 3H-thymidine and 3H-proline incorporation rates at 12 and 24 hours were determined in transected patellar tendon explants from young (21 days), intermediate age (8 to 10 weeks), and older (4 to 6 months) rats. In the second part, the same incorporation rates were measured in the older tendon explants in response to treatment with control medium, medium with a high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…In vitro studies revealed degenerative changes, reduced synthesis of collagen type I and proteoglycans, as well as decreased cell proliferation, viability and metabolism following glucocorticoid exposure [26][27][28][29][30]. Experimental evidence on the effects of steroids in combination with quinolones is even more limited.…”
Section: Page 5 Of 37mentioning
confidence: 99%
“…In vitro studies revealed degenerative changes, reduced synthesis of collagen type I and proteoglycans, as well as decreased cell proliferation, viability and metabolism following glucocorticoid exposure [26][27][28][29][30]. Experimental evidence on the effects of steroids in combination with quinolones is even more limited.…”
Section: Page 5 Of 37mentioning
confidence: 99%
“…16,17 The use of corticosteroids for chronic tendonitis is suspect, because this condition is degenerative rather than inflammatory. 2,18 Corticosteroids have been prescribed extensively for a multitude of conditions, and their side effects are well documented. Serious side effects are most likely with prolonged or high-dose use.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors believe there is no role for the use of oral corticosteroids in sports injuries. [1][2][3][4][5] In practice, although, it seems they are used frequently.…”
mentioning
confidence: 99%
“…3,16,31 This is thought to lead to focal degeneration and microtears in the tendon. 1,3,15,17,24,32 Many athletes are able to sustain these high forces and repetitive loads without developing patellar tendinopathy, but others develop this painful and debilitating syndrome. Some attribute the development of patellar tendinopathy to failed healing.…”
Section: Etiologymentioning
confidence: 99%